Successful thrombolysis of portal vein thrombosis induced by post-liver transplant splenectomy: a case report - Yan, Xu; Wang, Pusen; Huang, Yiming; Zhao, Dong; Zhong, Lin (Frontiers in Transplantation, 2025)
Introduction and importanceLiver transplantation (LT) is a life-saving procedure for patients with end-stage liver disease, but post-transplant complications, such as portal vein thrombosis (PVT), can significantly impact patient outcomes. PVT is particularly challenging when it occurs after splenectomy, which is sometimes necessary in LT recipients with persistent hypersplenism or thrombocytopenia. The optimal management of PVT in this context remains unclear, and further clinical insights are needed.Case presentationWe present a case of a 57-year-old male with a history of chronic hepatitis B-induced liver cirrhosis who underwent LT. Due to persistent hypersplenism and thrombocytopenia, the patient later underwent splenectomy. One month post-splenectomy, the patient developed PVT, which was initially managed with anticoagulation therapy (aspirin and rivaroxaban). Despite treatment, thrombosis progressed, requiring intravenous heparin and urokinase thrombolysis. Serial imaging confirmed thrombus resolution, and the patient was discharged on long-term anticoagulation therapy.Clinical discussionPVT following splenectomy in LT patients is a complex and potentially life-threatening condition influenced by altered portal hemodynamics and a hypercoagulable state. The standard treatment involves anticoagulation, but there is no consensus on the optimal regimen in post-transplant patients. This case highlights the potential efficacy of peripheral urokinase infusion as an alternative to interventional thrombolysis, particularly for patients who refuse invasive procedures. Long-term anticoagulation and close monitoring are crucial to prevent recurrence.ConclusionThis case underscores the importance of early detection, tailored anticoagulation strategies, and a multidisciplinary approach in managing PVT following splenectomy in LT recipients. Peripheral urokinase infusion may serve as a viable treatment option for patients with contraindications or reluctance toward invasive procedures. Further studies are needed to optimize anticoagulation protocols and long-term management strategies in this patient population.